(untitled) (Research, Society and Development, 2021)
The scientific research seeks to investigate the socio-environmental conflict in the Porto do Capim community located in the Varadouro neighborhood, João Pessoa/Paraíba through the municipal management verticalized in the environmental Public Civil Action. The methodology applied is called legal hermeneutics, which will be interpreted through technical reports and the Civil Inquiry. It is noted that the conflict exists because it is an environmental preservation area that can be transformed into an ecological park if the resident community, since the 1930s, is relocated. It appears that the Porto do Capim community was recognized through technical reports as it is a traditional community, which would give the right to decide, both through extravagant and alien legislation, where it wants to settle and continue with the customs. It is concluded that there are legal interconnections to give visibility to the two interests in order to strengthen environmental and cultural preservation, contributing to local strengthening.